Tailoring the thermal stability of nanocrystalline Ni alloy by thick grain boundaries. (June 2020) - Ding, Jie; Shang, Z.; Zhang, Y.F.; Su, R.; Li, Jin; Wang, H.; Zhang, X.
Abstracts: Nanocrystalline (NC) metals have high strength, but are highly susceptible to grain growth at elevated temperatures due to the driving force to reduce the energy stored at grain boundaries (GBs). In this study, we compared the thermal stability of NC Ni alloy with conventional thin GBs and thick GBs. Thermomechanical treatment was applied to induce thick GBs in the Ni alloy. After annealing at 800 °C, significant grain growth occurs in the Ni alloy with thin GBs; whereas the nanograins with Mo-rich thick GBs remain stable. This study provides a fresh perspective on improving the thermal stability of NC alloys. Graphical abstract: Image, graphical abstract